Pengaruh Fee Audit, Audit Tenure, dan Ukuran KAP terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sektor Property & Real Estate serta Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Hasanah Hasanah; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to investigate the impact of audit fees, audit tenure, and KAP size on audit quality. This research samples are property & real estate and infrastructure companies that are listed in Indonesia Stock Exchange during 2018-2022 periods, using the purposive sampling method. Audit quality’s proxy is earning surprise Benchmark. This research data used secondary data taken from the annual report published by the Indonesia Stock Exchange (IDX). Logistics regression analysis is used as data analysis techniques. This study implies a descriptive research design using a quantitative approach. This research finds that audit fees have positive effect on audit quality, audit tenure has no effect on audit quality, while KAP size has negative effect on audit quality.